Inertial Vibration Characteristics of Track Chassis Caused by Reciprocating Motion of Crank Slider - Zhong Tang; Yu Li; Yuepeng Zhou; Haotian Zhang (Shock and Vibration)
The crank slider of self-propelled baling machinery is used for straw compression on the crawler chassis structure. During the reciprocating motion of the crank slider, the inertia of the piston will cause a greater shock to baling machinery. In this paper, the inertia of the crank slider piston was analyzed on crawler chassis. The model and parameter values of the inertia force balance of the crank slider were established by the complete balance method. The test mode was used to analyze the natural mode and mode shape of the piston. The vertical vibration amplitudes of the crawler chassis beam were tested and used to reflect the specific inertial vibration characteristics of the self-propelled baling machinery caused by the reciprocating motion of the piston. The inertial vibration caused by the reciprocating motion of the crank slider was eliminated by the method of weighting the tail of the track beam. Results indicated that the self-balancing counterweight of the crank slider was 261.82 kg. The six natural modal frequencies of the piston were 4.62, 17.26, 29.82, 63.85, 83.73, and 141.58 Hz, respectively. During the reciprocating motion of the piston, the first-order frequency of the piston would be excited by feeding auger excitation frequency of 3.77 Hz and may cause resonance. And, the vertical vibrates of track beam was based on the measuring point 6 as a fulcrum. Adding a counterweight of 265 kg at the end of the track chassis would completely eliminate the self-propelled baling machinery inertial vibration caused by the reciprocating motion of the crank slider.